Strategy for Decreasing the Rate of Stunting Through Early Childhood Health and Nutrition Training for Tutors/Parents of Early Childhood Education - Yenina Akmal; Hikmah Hikmah; Ika Subekti; Ichtineza Halida Hardono (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2020)
Stunting also occurs in urban areas, i.e., DKI Jakarta. East Jakarta is the second-highest (25.7%) location where stunting occurred. Since this activity was conducted in Duren Sawit Subdistrict, where numerous people still received Healthy Jakarta Cards, special efforts were needed to reduce the high stunting rate. The method used is qualitative descriptive. The form of training is the participant observation method and demonstration, include cooking demonstrations and Focus Group Discussion (FGD). This efforts made to decrease the number of Stunting in Duren Sawit Subdistrict. The training was given to 35 ECE tutors and parents of students from various ECE in Duren Sawit Subdistrict. Tutors and parents seemed enthusiastic and active during the activities, especially when they were given the task to create a one-week healthy menu in groups and then closed with a demo of making a cake with purple sweet potato as ingredients.